Antibacterial and Antioxidant Activities of Novel Actinobacteria Strain Isolated from Gulf of Khambhat, Gujarat - Dholakiya, Riddhi N.; Kumar, Raghawendra; Mishra, Avinash; Mody, Kalpana H.; Jha, Bhavanath (Frontiers in Microbiology, 2017)
In this study, a gram positive marine Actinobacteria was isolated from sea sediment which showed 84% 16S rRNA gene sequence (KT588655) similarity with Streptomyces variabilis (EU841661), and designated as Streptomyces variabilis RD-5. The genus Streptomyces is considered as a promising source of bioactive secondary metabolites. The BIOLOG based analysis suggested that S. variabilis RD-5 utilised a wide range of substrate compared to the reference strain. The result is further supported with statistical analysis such as AWCD (average well colour development), heat-map and PCA (principal component analysis). The whole cell fatty acid profiling showed the dominance of iso/anteiso branched C15-C17 long chain fatty acids. The identified S. variabilis RD-5 strain showed a broad spectrum of antibacterial activities against the Gram-negative bacteria (Escherichia coli NCIM 2065, Shigella boydii NCIM, Klebsiella pneumoniae, Enterobacter cloaceae, Pseudomonas sp. NCIM 2200 and Salmonella entertidis NCIM), and Gram-positive bacteria (B. subtilis NCIM 2920 and Staphylococcus aureus MTCC 96). Extract of S. variabilis strain RD-5 showed 82.86 and 89% of DPPH free radical scavenging and metal chelating activity respectively at 5.0 mg/mL. While H2O2 scavenging activity was 74.5% at 0.05mg/mL concentration. Furthermore, polyketide synthases (PKSs type I and II), an enzyme complexes that produce polyketides, encoding gene(s) were also detected in strain RD-5 which may possibly be responsible for the production of antibacterial compound(s). In conclusion, a novel bacterial isolate of Actinobacteria was isolated from the unexplored sea sediment of Alang, Gulf of Khambhat (Gujarat), India which showed promising antibacterial activities. However, fractionation and further characterization of active compounds from S. variabilis RD-5 is needed for their optimum utilization towards antibacterial purposes.